The role of remote sensing and geographic information systems techniques in detecting and analyzing the change in vegetation cover in Najaf Governorate using the (NDVI and SAVI) indicators - Al-Zurfhi, Hawraa Radhi Jasim; Al-Jassani, Nisreen Awwad; Al-Shammari, Hussein Musa (Al-Adab Journal, 2021)
This study aims to use remote sensing technology and geographic information systems to detect changes in vegetation cover in Najaf Governorate for the period (1984-2018), through digital processing of five satellite visuals (Landsat8, 8-5) for the years (1984, 1988 and 1998, 2008 and 2018) through the use of the Natural Change Index for Green Plants (NDVI) and (SAVI), where these visuals were downloaded for free from the US Geological Survey UCGS website, then processed and analyzed these visuals through the GIS program. The study showed a significant decline of vegetation cover in Najaf Governorate during the study period, according to the data of the vegetation cover indicators (NDVI) and the modified soil vegetation index (SAVI). The level of lands with low vegetation cover the largest area among the levels، which amounted to (27821.6, 27849.5, 2899.8, 28283.8 and 27634.0 km2) for the years 1984, 1988, 1998, 2008 and 2018, respectively, which are located within the western plateau region, as for the modified plant index of soil (SAVI) The level of highly degraded lands occupied most of the area of ​​the study area, reaching about (28348.1, 28007.7, 28318.7, 28226.7 and 27916.6 km2) for the years 1984, 1988, 1998, 2008 and 2018, respectively.